2017
DOI: 10.3389/fnbeh.2017.00034
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Effects of NMDA-Receptor Blockade on Extinction Learning and Related Brain Activation Are Modulated by BMI

Abstract: A distributed network including prefrontal and hippocampal regions is involved in context-related extinction learning as well as in renewal. Renewal describes the recovery of an extinguished response if the context of extinction differs from the context of recall. Animal studies have demonstrated that prefrontal, but not hippocampal N-methyl-D-aspartate receptor (NMDAR) antagonism disrupted extinction learning and processing of task context. However, human studies of NMDAR in extinction learning are lacking, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 86 publications
(144 reference statements)
1
4
0
Order By: Relevance
“…Retrieval elicited BOLD activation in right posterior hippocampus and deactivation in bilateral anterior hippocampus. Correspondingly, in previous studies hippocampal activation during encoding and recall was predominantly located in posterior regions (e.g., Lissek et al, 2015a, 2017, 2018; Golisch et al, 2017), suggesting that generally, encoding and recall in contextual associative learning recruit similar regions as the above mentioned visuospatial task. So in the light of the findings by Duarte et al, the hippocampal activation pattern in ATO REN lacked the right posterior component important for encoding and retrieval, which presumably modulated or weakened these processes and thus impaired extinction context encoding in a way that had an adverse impact upon response selection in recall.…”
Section: Discussionsupporting
confidence: 64%
“…Retrieval elicited BOLD activation in right posterior hippocampus and deactivation in bilateral anterior hippocampus. Correspondingly, in previous studies hippocampal activation during encoding and recall was predominantly located in posterior regions (e.g., Lissek et al, 2015a, 2017, 2018; Golisch et al, 2017), suggesting that generally, encoding and recall in contextual associative learning recruit similar regions as the above mentioned visuospatial task. So in the light of the findings by Duarte et al, the hippocampal activation pattern in ATO REN lacked the right posterior component important for encoding and retrieval, which presumably modulated or weakened these processes and thus impaired extinction context encoding in a way that had an adverse impact upon response selection in recall.…”
Section: Discussionsupporting
confidence: 64%
“…For example, while ketamine diminishes the amplitude of the so-called mismatch negativity (MMN) EEG response to (auditory) oddball stimuli (Rosburg & Kreitschmann-Andermahr, 2016), a single dose of memantine enhances MMN amplitude (Korostenskaja et al, 2007; Light et al, 2017; Swerdlow et al, 2016). Although memantine was found to impair learning as well as markers of perceptual and neural processing in some tasks (e.g., Rammsayer, 2001, 2006; Schugens et al, 1997), most studies found memantine to improve learning and to boost perceptual and neural processing, including EEG markers of the excitation-inhibition (E/I) balance (1/f slope) (Golisch et al, 2017; Korostenskaja et al, 2007; Light et al, 2017; Swerdlow et al, 2016, 2020). As these previous studies typically used auditory stimuli, our results with visual stimuli add to a growing body of literature indicating that memantine can enhance sensory function, instead of decreasing it, and is the first study explicitly linking memantine to recurrent processing.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological manipulation of NMDA receptors modulated extinction related to nonaversive learning in human subjects when conducted within the same context as for initial acquisition: strikingly both the NMDA receptor agonist, D-cycloserine, DCS, (Klass et al, 2017) and the NMDA receptor antagonist, memantine (Golisch et al, 2017), enhanced extinction learning. This latter finding, which was associated with dose-related effects of memantine modulated by body mass index, suggests that finetuning of the degree of activation of NMDA receptors is a key facet of effective extinction learning.…”
Section: Neurotransmitter Systems Involved In Extinction and Renewal mentioning
confidence: 97%
“…Each compound is associated with a specific outcome. Following an intertrial interval of 5-9 s, one cue/context compound is presented for 3 s. Then, a question appears asking the participant to predict whether consumption of the food in the restaurant will cause stomachache in a hypothetical patient, followed by a response period of maximally 4 s. Feedback, providing the correct answer, is then shown for 2 s (Golisch et al, 2017). B.…”
Section: Brain Regions Involved In Extinction and Renewal Of Nonaversmentioning
confidence: 99%
See 1 more Smart Citation